Myocardial ischaemia as a result of external coronary compression from infective aortic root aneurysm: atypical presentation of prosthetic valve endocarditis. Issue 2 (June 2018) - Sekar, Baskar; Wheeler, Richard; Masani, Navroz; Gallagher, Sean
Summary: This case describes an unusual presentation of prosthetic valve endocarditis (PVE): an acute coronary syndrome. A 67-year-old male presented with cardiac sounding chest pain on a background of a short history of night sweats, weight loss and general malaise. Four months previously, he had undergone bio-prosthetic aortic valve replacement for severe aortic stenosis and single vessel bypass grafting of the obtuse marginal. Whilst having chest pain, his ECG showed infero-lateral ST depression. Early coronary angiography revealed a new right coronary artery (RCA) lesion that was not present prior to his cardiac surgery. Using multi-modality cardiac imaging, the diagnosis of PVE was made. An aortic root abscess was demonstrated that was causing external compression of the RCA. Learning points: PVE accounts for up to 20% of all cases of infective endocarditis. High clinical suspicion and early blood cultures before empirical antibiotics are key as the presentation of PVE can often be atypical. PVE rarely presents as an acute coronary syndrome. Potential mechanisms by which PVE may result in an ACS include coronary embolization, obstruction of coronary ostia by a large mobile vegetation and external coronary artery compression from an infective aneurysms/abscess. Repeat cardiac surgery is often required for high-risk PVE such as those caused by staphylococcal infection or severe prosthetic dysfunction.